Pengaruh Pendapatan Asli Daerah, Dana Bagi Hasil dan Belanja Modal terhadap Kemandirian Keuangan pada Pemerintah Daerah Kabupaten/Kota di Provinsi Kalimantan Timur Tahun 2019-2023 - Evi Zunnia; Sri Hartaty; Eka Jumarni Fithri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the influence of local revenue, profit-sharing funds, and capital expenditure on financial independence in Regency/City Regional Governments in East Kalimantan Province. The data used in this study is secondary data with data obtained through the official website of the Central EPPID of the Audit Board of the Republic of Indonesia (BPK RI) in 2019-2023. This type of research is a quantitative research. The population that is the focus of this study includes all Regional Governments, consisting of 9 Regencies/Cities in East Kalimantan Province with a total sample of 45 in this study. The sample determination in this study used the "purposive sampling" technique. The data analysis method uses panel data regression analysis with the help of Eviews 12 for windows. The results of this study can be concluded that partially local original revenue and profit-sharing funds have no effect on financial independence, while capital expenditure has a negative and significant effect on financial independence. Simultaneously, local revenues, profit-sharing funds, and capital expenditure have a significant effect on financial independence in Regency/City Regional Governments in East Kalimantan Province in 2019-2023.